Does a video module improve patient adherence to recommended gestational weight gain guidelines?. (31st December 2023) - Milone, Gina F.; Tiwari, Mahesh; Mclnerney, Hailey J.; Franz, Brynn; Chappelle, Joseph; Persad, Malini D.; Herrera, Kimberly M.
Abstract: Objectives: We aim to assess if implementation of an educational video module can improve patient adherence to recommended weight gain guidelines. Secondarily, we investigated if patients' knowledge about gestational weight gain was improved with use of the video, as well as if there was a difference in maternal and neonatal outcomes, and patient satisfaction. Methods: This was an IRB-approved, prospective cohort study conducted from February 2019 to October 2019. Patients were recruited from a large academic practice during their first trimester of pregnancy. Patients in the control cohort received routine care. Patients in the video cohort watched a 5-min educational video module about gestational weight gain. Pre-pregnancy weight and baseline demographics were recorded. All patients took a baseline questionnaire assessing gestational weight gain knowledge upon enrollment, and again 4 weeks later. Pre and post score differences were calculated. On admission to the hospital for delivery, all patients' gestational weight gain was calculated, and the overall gestational weight gain differences between the two groups were calculated. Maternal and neonatal delivery outcomes were also collected. T -tests, Mann-Whitney U tests, and Chi-square analyses were used to compare groups, and a p -value of <.05 was deemed statistically significant. Results: During the study period, 155 patients were recruited, with 79 in control cohort and 76 in video cohort, respectively. There was no significant difference in the percentage of patients who gained the appropriate amount of weight between the two groups; 25% (18/74) of patients in the control vs. 25% (17/68) of patients in video cohort ( p  = .926). There was no difference in the improvement of the pre and post assessment scores when compared between the two cohorts; the average score improvement was 1.72 ± 15.09% for the control, vs. 6.20 ± 12.51% for video cohort ( p  = .129). There was no difference in maternal or neonatal outcomes between the two groups. Patients were overall satisfied with the video module, with 67.6% ( n  = 45) reporting the video to be very educational. Conclusions: Use of a video module did not improve GWG outcomes or knowledge in our study. Future work can focus on use of a recurring intervention throughout pregnancy, either with app-based technology or multiple videos.